2019
DOI: 10.3389/fphys.2019.01356
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Smoking Habit and Sperm Parameters Among Patients Attending an Infertility Clinic

Abstract: BackgroundThis study aimed to estimate stress markers, oxidative stress (OS), reproductive hormones and sperm parameters in male smokers and non-smokers and observe the impact of oxidative stress markers and smoking on sperm count, motility and morphology in a selected population of Karachi, Pakistan.MethodsThis cross-sectional study was conducted from July 2017 to July 2018 at Aga Khan University (AKU), in Karachi, Pakistan. The subjects were recruited from the Sindh Institute of Reproductive Medicine (SIRM),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 32 publications
2
25
1
2
Order By: Relevance
“…The results of the current study agreed with the results of the study conducted by [32], and differed with the results of the study conducted by [33]. Many other studies have shown that the relationship of smoking and male infertility is uncertain, ie.…”
Section: Hormonal Levels Of Infertile Males According To Smokingsupporting
confidence: 58%
“…The results of the current study agreed with the results of the study conducted by [32], and differed with the results of the study conducted by [33]. Many other studies have shown that the relationship of smoking and male infertility is uncertain, ie.…”
Section: Hormonal Levels Of Infertile Males According To Smokingsupporting
confidence: 58%
“…A large number of studies have associated smoking with poorer sperm quality ( 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ) and suggested that quitting tobacco use and improving general lifestyle would improve male fertility. Sharma et al ( 44 ) conducted a large meta-analysis of the effects of cigarette smoking and reported that moderate and heavy smoking affected sperm count, motility, and morphology.…”
Section: Smokingmentioning
confidence: 99%
“…(1) Fertility Very common habits, like smoking or alcohol intake, could influence paternal sexual functions at different levels. Studies suggest a detrimental effect of tobacco smoking mediated by reduced sexual hormones levels and exposure of spermatozoa to oxidative stress [41,42]. Heavy smokers present lower sperm concentration, total count and more pronounced teratozoospermia which entail decreased ART success rates although effects on sperm motility are found unaffected [41,43].…”
Section: ) Lifestyle Paternal Factorsmentioning
confidence: 99%